G389(P) Enhancing communication and training opportunities in paediatrics. (25th October 2020) - McDermott, H; Duthie, L; Kelly, L; Vawda, H; Hine, C; Darbyshire, A; Brothwell, S; Syrimi, E; Reunis, E; Coakley, H; Goodyear, H
Abstract : Aims: Historically, communication about regional training and educational opportunities relied on emails from the school administrator, programmes or assessments teams. This resulted in not all being aware of information. Therefore, in 2018, the Head of School (HoS) and trainees' committee (TC) devised innovative approaches. Methods: The TC and HoS had meetings to discuss methods of improving communication and standardising trainees' expectations, particularly regarding the Annual Review of Competency Progression (ARCP). We created and implemented an 'ARCP checklist' for trainees and trainers of expected eportfolio entries, which was aligned with RCPCH requirements in 2018–19. We planned and implemented a regional trainees' website and investigated various communication methods to enhance trainee engagement and minimise time spent searching for information. In August 2019, we distributed a snapshot survey via social media (Whatsapp groups and Facebook) and at protected teaching days using online platform Survey Monkey to assess trainees' experience and gain feedback. Results: The regional trainees' website has clearly laid out information updated weekly by the TC. This includes educational and research opportunities, courses, teaching resources and how to apply for academic and less than full time training, plus return to work programmes. All regional paediatricians receive a monthly newsletter produced by the HoS with essential information including training updates, educational courses and opportunities, supervisor training and trainee-led research. We created a Twitter account to further disseminate information. Feedback: The survey had 41 responses (14% of trainees) with at least one response from each training year. Most (17) responses were from ST4-5. Of the 37 (90%) who had used the website, 35 (94%) found it 'quite' or 'extremely useful'. The ARCP checklist was frequently mentioned as one of the most useful changes implemented. 38 (93%) read the newsletter and the majority (86%) found it 'quite' or 'extremely useful'. Fewer (54%) trainees were aware of the Twitter account. 30/38 trainees (79%) reported the changes had improved trainee experience compared to before these resources were available. Conclusion: By embracing technology and close liaison between TC and school board, our regional communication and trainee experience has been significantly enhanced. We recommend this to all paediatricians.